Xét \(x^2-2=0\)
\(\Rightarrow x^2=0+2\)
\(\Rightarrow x^2=2\)
\(\Rightarrow\orbr{\begin{cases}x=-\sqrt{2}\\x=\sqrt{2}\end{cases}}\)
Vậy \(\orbr{\begin{cases}x=-\sqrt{2}\\x=\sqrt{2}\end{cases}}\)là nghiệm của đa thức \(x^2-2\)
b ) Xét \(\left(4x-3\right)\left(5+x\right)=0\)
\(\Rightarrow\orbr{\begin{cases}4x-3=0\\5+x=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}4x=3\\x=-5\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=\frac{3}{4}\\x=-5\end{cases}}\)
Vậy \(\orbr{\begin{cases}x=\frac{3}{4}\\x=-5\end{cases}}\)là nghiệm của đa thức \(\left(4x-3\right)\left(5+x\right)\)
Chúc bạn học tốt !!!
+ x2 - 2
Ta có \(f\left(x\right)=x^2-2\)
Khi f (x) = 0
=> \(x^2-2=0\)
=> \(x^2=2\)
=> \(x=\pm\sqrt{2}\)
Vậy f (x) có 2 nghiệm: x1 = \(\sqrt{2}\); x2 = \(-\sqrt{2}\).
+ (4x - 3) (5 + x)
Ta có \(g\left(x\right)=\left(4x-3\right)\left(5+x\right)\)
Khi g (x) = 0
=> \(\left(4x-3\right)\left(5+x\right)=0\)
=> \(\orbr{\begin{cases}4x-3=0\\5+x=0\end{cases}}\)=> \(\orbr{\begin{cases}4x=3\\x=-5\end{cases}}\)=> \(\orbr{\begin{cases}x=\frac{3}{4}\\x=-5\end{cases}}\)
Vậy đa thức f (x) có 2 nghiệm: x1 = \(\frac{3}{4}\); x2 = -5.